(untitled) (Research, Society and Development, 2022)
Leishmaniasis is a parasitic disease that affects worldwide populations, research has indicated the use of polymeric nanoparticles for the treatment of that pathology. Thus, this work aimed to carry out a scientific and technological prospection of the antileishmanial activity of polymeric nanoparticles produced with carboxymethylated cashew gum. For this, a search was carried out in databases of publication of articles and patents with keywords and specific criteria, taking into account only those that presented correlations with the research topic. The results obtained from the search for articles and patents reveal that carboxymethylated cashew gum has few studies and no patented technology focused on nanotechnology, and no work/document has elucidated the potential of these materials to combat leishmaniasis. Thus, it is concluded that there are few investigations developed based on carboxymethylated cashew gum, especially when related to nanotechnology, providing opportunities for new research and products with this biomaterial to be explored.